A Comparative Investigation of Firms' Innovative behaviors During Different Stages of the Cluster Life-Cycle (Cover study for PhD dissertation) - Sam Tavassoli (European Regional Science Association (ERSA), 2010)
The PhD dissertation aims to investigate/measure 'innovative behaviors' of firms by comparing clustered versus non-clustered firms along various stages of (standardized) cluster life cycle in ICT sector within various Nordic countries/regions. In order to be able so, the theoretical platform is developed to capture the desirable range of innovative behaviors of firms, on one hand, and evolutionary path of cluster on the other hand. The former encompass Innovation activities (as input behavior), i.e. both R&D/non-R&D activities (expenditure), introduction of four types of innovation based on last version of Oslo Manual (as output behavior), and sales of innovative product (as ultimate output behavior). The later includes five possible scenarios for cluster evolution intertwining life cycle stages, which to be elaborated by both qualitative meta-analysis and simulation method. The innovation-related data will be based on CIS 2008 and subject approach is applied to measure innovative behavior. Each comparative (empirical) paper devoted to specific cluster life cycle stage. In line with mentioned comparison, this dissertation seeks to explore the correlation between 'innovation activities', 'innovation introduction', and 'sales' by regression and sensitivity analysis. Moreover, some hypothesis regard to innovation introduction will be examined deeply, e.g. clustered firms show more product innovation and non-clustered firms show more process innovation.
Keywords: 330